PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IV SD NEGERI 010 SILIKUAN HULU - Edi Sutrisna (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes in Social Sciences (IPS) at SD Negeri 010 Silikuan Hulu. This is characterized by the average student score of 64.34. Furthermore, the completeness of student learning outcomes is only 40.63%, representing only 13 out of 32 students. The low performance in this subject was attributed to several factors: (a) teachers lacking mastery of the subject matter; (b) teachers primarily using the lecture method; (c) teachers not utilizing instructional media; and (d) Social Sciences learning being predominantly teacher-centered. To address these problems, the researchers implemented improvements in learning through classroom action research, applying the Two Stay Two Stray cooperative learning model. This study was conducted over two cycles, with each cycle consisting of two meetings and one daily test. Data collection techniques included observation of student and teacher activities, as well as achievement tests. The results indicated that the application of the Two Stay Two Stray cooperative learning model can increase the activity of teachers and students, as well as students' learning outcomes in Social Sciences. This is supported by the following findings: (a) an increase in the activity of both teachers and students from the first cycle to the second cycle. Teacher activity increased from 61.60% in the first cycle to 81.25% in the second cycle, representing an increase of 19.65%. Student activity increased from 61.61% in the first cycle to 82.14% in the second cycle, with an increase of 20.53%; and (b) an increase in student learning outcomes from a baseline average of 64.34. In the first cycle, the average increased to 68.75, and in the second cycle, it further increased to 76.86.